Persistent clinical symptoms and their association with CM syndromes in post-COVID-19 rehabilitation patients in Hong Kong - Zhong, Linda (2023)
Background: Heterogeneous clinical conditions were observed in individuals who had recovered from COVID-19 and some symptoms were found to persist for an extended period post-COVID. Given the non-specific nature of the symptoms, Chinese medicine (CM) is advantageous in providing holistic medical assessment for individuals experiencing persisting problems. Chinese medicine is a type of treatment that involves prescribing regimens based on CM Syndromes diagnosed by CM practitioners. However, inadequate research on CM elements behind the practice has faced scrutiny. Methods: This study analysed 1058 CM medical records from 150 post-COVID-19 individuals via a semi-text-mining approach. A logistic model with MCMCglmm was then utilised to analyse the associations between the indicated factors and identified conditions. Calculations were performed using R Studio and related libraries. Results: With the semi-text-mining approach, three common CM Syndromes (Qi and Yin Deficiency, Lung and Spleen Deficiency, Qi Deficiency of both Spleen and Lung) and nine clinical conditions (fatigue, poor sleep, dry mouth, shortness of breath, cough, headache, tiredness, sweating, coughing phlegm) were identified in the CM clinical records. Analysis via MCMCglmm revealed that the occurrence of persisting clinical conditions was significantly associated with female gender, existing chronic conditions (hypertension, high cholesterol, and diabetes mellitus), and the three persisting CM Syndromes. The current study triangulated the findings from our previous observational study, further showing that patients with certain post-COVID CM Syndromes had significantly increased log-odds of having persisting clinical conditions. Furthermore, this study elucidated that the presence of chronic conditions in the patients would also significantly increase the log-odds of having persistent post-COVID clinical conditions. Conclusion: This study provided insights on mining text-based CM clinical records to identify persistent post-COVID clinical conditions and the factors associated with their occurrence. Future studies could examine the integration of integrating exercise modules, such as health qigong Liuzijue, into multidisciplinary rehabilitation programmes.